2015
DOI: 10.1016/j.proci.2014.06.123
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved spatial patterns and interactions of soot, PAH and OH in a turbulent diffusion flame

Abstract: Soot control raises important fundamental issues and industrial challenges, which require a comprehensive understanding of processes governing its formation, interactions and destruction in turbulent flames. A physical insight of the soot space-time evolution in a turbulent diffusion flame is reported in this article by combining three simultaneous high sampling rate imaging diagnostics operating at a frame rate of 10 kHz: light scattering from soot particles, planar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
3
34
0
2
Order By: Relevance
“…Soot volume fraction appears in the form of layers of approximately 0.5-2.5 mm thickness, which are clearly distinguishable and comparable to previous 1 The immediate vicinity of the wall is not accessible due to the limitation of the optical access, reducing the field of view by about 5 mm for each side. experiments [4,6]. A close-up view of these ligaments is presented for two HABs in Fig.…”
Section: Soot Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Soot volume fraction appears in the form of layers of approximately 0.5-2.5 mm thickness, which are clearly distinguishable and comparable to previous 1 The immediate vicinity of the wall is not accessible due to the limitation of the optical access, reducing the field of view by about 5 mm for each side. experiments [4,6]. A close-up view of these ligaments is presented for two HABs in Fig.…”
Section: Soot Structurementioning
confidence: 99%
“…In addition to the many studies carried out on sooting laminar flames, it is worth examining soot production in turbulent flows that are widely used in industrial applications. In this respect, much of the technical literature has focused on soot in turbulent jet diffusion flames [4][5][6][7][8]. This case has been extensively investigated with a variety of diagnostics, highlighting the effects of turbulent eddies, strain rate and scalar dissipation on the soot volume fraction f v distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Although laminar flame (e.g., Karataş & Gülder 2012) and turbulent flame (e.g., Coppalle & Joyeux 1994, Kent & Honnery 1987) experiments had been conducted in the past, the tremendous advancement of laser diagnostics has allowed much more detailed measurements recently (e.g., Desgroux et al 2013, Franzelli et al 2015, Mahmoud et al 2015, Narayanaswamy & Clemens 2013, Zhang et al 2011. Of particular interest are simultaneous measurements, in which two or more flow quantities are measured to provide joint statistics.…”
Section: Sooting Flamesmentioning
confidence: 99%
“…Of particular interest are simultaneous measurements, in which two or more flow quantities are measured to provide joint statistics. Examples include the velocity-soot volume fraction (Narayanaswamy & Clemens 2013), velocity-OH (Geigle et al 2013, PAH-OH (Franzelli et al 2015), and temperature-soot volume fraction (Chan et al 2011). Apart from the macroscopic comparison of soot or composition fields, quantitative simultaneous measurements allow specific assumptions about the turbulence and its influence on chemistry to be validated.…”
Section: Sooting Flamesmentioning
confidence: 99%
“…This requires time-resolved LII measurements, where the temporal evolution of the soot structures can be tracked. Franzelli et al recently reported 10 kHz measurements of soot structures with soot scattering simultaneous with polycyclic aromatic hydrocarbon (PAH) and OH fluorescence, but they did not address in detail the potential for quantitative soot volume fraction measurements [30]. There are relatively few reports of high-repetition rate LII studies in which the effects of repetitive pulsing on soot physical characteristics have been evaluated.…”
Section: Introductionmentioning
confidence: 99%